2021
DOI: 10.1177/87560879211026010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations on a high-density polyethylene (HDPE) blown film cooling with a new design of the counter-flow/radial jet air-ring

Abstract: This study experimentally and numerically investigates a typical HDPE blown film production process cooled via a single-lip air-ring. The processing observations are considered for the proposed subsequent modifications on the air-ring design and the location relative to the die to generate a radial jet, directly impinging on the bubble. Measurements are performed to collect the actual operating parameters to set up the numerical simulations. The radiation heat transfer and the polymer phase change are consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It was found that only the Muslet & Kamal heat transfer model was correctly able to capture the physical characteristics of the heat transfer between the bubble and the cooling air, especially in the case of a very high FLH. Moreover, Ismail, ME [43] performed numerical and experimental investigations on the external cooling of an HDPE bubble with a new design of a counter flow air ring design. The performance of four different two-equation-based turbulence models is compared to the experimental results of the measured air velocity via a five-hole pitot tube.…”
Section: The Inlet Cooling Airflow Rate Calculationsmentioning
confidence: 99%
“…It was found that only the Muslet & Kamal heat transfer model was correctly able to capture the physical characteristics of the heat transfer between the bubble and the cooling air, especially in the case of a very high FLH. Moreover, Ismail, ME [43] performed numerical and experimental investigations on the external cooling of an HDPE bubble with a new design of a counter flow air ring design. The performance of four different two-equation-based turbulence models is compared to the experimental results of the measured air velocity via a five-hole pitot tube.…”
Section: The Inlet Cooling Airflow Rate Calculationsmentioning
confidence: 99%
“…The uniformity of film thickness is mainly affected by two aspects: the structure of the blown film die, and the air blowing process . Numerous studies have investigated the aerodynamic phenomena resulting from different cooling rings on the cooling efficiency in blown film extrusion. , In contrast, reports of improvements in the structure of blown film die are seldom seen in recent decades. The development of blown film die structure is almost at a standstill.…”
Section: Introductionmentioning
confidence: 99%